Cybersecurity for distributed energy resources and smart inverters. Issue 1 (1st December 2016) - Qi, Junjian; Hahn, Adam; Lu, Xiaonan; Wang, Jianhui; Liu, Chen‐Ching
Abstract : The increased penetration of distributed energy resources (DER) will significantly increase the number of devices that are owned and controlled by consumers and third‐parties. These devices have a significant dependency on digital communication and control, which presents a growing risk from cyber‐attacks. This study proposes a holistic attack‐resilient framework to protect the integrated DER and the critical power grid infrastructure from malicious cyber‐attacks, helping ensure the secure integration of DER without harming the grid reliability and stability. Specifically, the authors discuss the architecture of the cyber‐physical power system with a high penetration of DER and analyse the unique cybersecurity challenges introduced by DER integration. Next, they summarise important attack scenarios against DER, propose a systematic DER resilience analysis methodology, and develop effective and quantifiable resilience metrics and design principles. Finally, they introduce attack prevention, detection, and response measures specifically designed for DER integration across cyber, physical device, and utility layers of the future smart grid.